Susceptibility of wheat to Bipolaris sorokiniana and its toxin measured through electrolyte leakage, chlorophyll loss and callus response - R. AGGARWAL* and DV. SINGH, A. SRINIVASAN, KD. SRIVASTAVA, (Indian Phytopathology, 2008)
The membrane injury of wheat measured through electrolyte leakage after inoculation with Bipolaris sorokiniana and infiltration with toxic culture filtrate showed a correlation of 0.94 and can be used as an index of susceptibility of wheat to B. sorokiniana. The pathogen as well as its toxic culture filtrate reduced more chlorophyll content of susceptible cultivars than resistant ones. The toxic culture filtrate significantly reduced the callus growth of wheat cultivars. The fresh weight loss was useful in differentiating susceptible and resistant cultivars and can be employed to screen resistant calli lines against B. sorokiniana.